Amatör Gökbilimde Üniversitelerin Yeri - Evren, Serdar (İstanbul Kültür Üniversitesi Yayınları, 2005)
Üniversitelerimizin astronomi bölümleri yaklaşık 50 yıldan beri halkın astronomiye ve fen bilimlerine ilgisini ve sevgisini arttırabilmek için büyük çaba sarfetmişlerdir. Değişik alanlarda yapılan çalışmaların başında amatör astronomlara yönelik dergi faaliyetleri ve yaz okulları gelir. Bu alanda en etkin çalışmayı Ege Üniversitesi Astronomi Bölmü öğretim elemanları ve öğrencileri son 14 yıldır yüzlerce kişi yetiştirmiştir. Yaz okullarına katılan kursiyerlerin %50’sinin 18-50 yaş arasında olması, kursiyerlerin çalışmalarına rahatlıkta sürdürebilecek yaşta ve beceri de olduklarını gösterir. Bu faaliyetleri yakından izleyen amatörlerden bazıları kendi teleskoplarıyla çeşitli çalışmalara başlamışlardır. Bu çalışmaların bir kısmı dergilerde yayınlanmıştır. Yıllar süren uğraş sonucunda Amatör Astronomi Derneği de kurulmuştur. Profesyoneller, artık amatörlerin daha üretken olmasını beklemektedir. Amatörlerin gökbilimine gözlemleriyle sağlayacakları destek birçok yıldızın gizemi çözebilecektir.

The astronomy departments of the universities in Turkey have made great effort in the last 50 years to increase the concern and sympathy of the public in the field of astronomy and in science as well. Puplishing some periodicals and organizing summer schools are main activities among these. The staff and the students of the Astronomy Department of Ege University have assumed a leading rolle during the last 14 years and trained hundreds of people. 50% of the participants of the organized summer schools are between 18-50 years of age and this fact indicates that they are well able to continue their work themselves. Some of the people who followed these activities have started working on various topics with their own telescopes. Some of these Works have already been publised in variouns magazines. A “society of amateur astronomers” has also been establised after a long-lasting effort. Professional astronomers are looking for more productive amateurs from now on. The support which the amateurs will provide with their observations will help in solving the mysteriouns behavior of many stars.
Keywords: Gökbilim; Üniversitelerde Astronomi; Amatör Gökbilim; Astronomi Bölümü; Astronomy; Astronomy at Universities; Amateur Astronomy; Astronomy Department